(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
With over a third of global energy used for building construction and operation, an optimum design for building envelopes is essential to improve the energy performance of the existing buildings. This study revealed that typical government high-rise office buildings in Malaysia have an average Building Energy Intensity (BEI) of 161 kWh/m2/year before any upgrading works on the air-conditioning and mechanical ventilation (ACMV) systems were conducted. This value is higher than the recommended value in Green Building Index (GBI) for commercial office buildings (150 kWh/m2/year) and the Economic Planning Unit (EPU) standard for public buildings (140 kWh/m2/year). Therefore, this study employed a case study approach combined with calibrated computer simulation to determine the optimal building envelope retrofit strategies and identify the three levels of interventions (minor, moderate and major levels) with corresponding energy reduction. A validated model representing a typical existing government high-rise office building in Malaysia was chosen as the base case model for energy evaluation studies. The effectiveness of each level of intervention and its energy retrofit measures (ERMs) were evaluated compared to the actual electricity bills. The results showed that all levels of interventions provided between 4% to 7% savings in annual energy consumption. The proposed interventions demonstrated compliance with the BEI benchmark margins of the GBI and EPU standard, namely 116 kWh/m2/year (minor intervention level), 113 kWh/m2/year (moderate intervention level), and 110 kWh/m2/year (major intervention level).